EFFECTS OF DAPAGLIFLOZIN IN HIGH AND LOW DIETARY SALT INTAKE PATIENTS WITH ALBUMINURIC DIABETIC KIDNEY DISEASE: A SUBANALYSIS OF THE Y-AIDA STUDY. (April 2021) - Kinguchi, Sho; Wakui, Hiromichi; Misumi, Toshihiro; Azushima, Kengo; Yamanaka, Takeharu; Terauchi, Yasuo; Tamura, Kouichi
Abstract : Objective: Current guidelines recommend the intensive control of BP as well as blood glucose to reduce albuminuria and prevent the development of diabetic kidney disease (DKD). We reported that improved home BP profile with dapagliflozin is independently associated with amelioration of albuminuria in Japanese patients with DKD (Kinguchi, et al. Cardiovasc Diabetol. 2019). The aim of this subanalysis was to investigate the differences in home BP lowering effects between high and low dietary salt intake patients with albuminuric DKD. Design and method: The Yokohama Add-on Inhibitory efficacy of Dapagliflozin on Albuminuria in Japanese patients with type 2 diabetes (Y-AIDA) study was a prospective, multicenter, single-arm study. A total of 86 T2DM (HbA1c 7.0–10.0%) individuals with albuminuric DKD (UACR > = 30 mg/gCr, eGFR > = 45 ml/min/1.73m2) were enrolled, and 85 participants were administered with add-on dapagliflozin for 24 weeks. Subgroup analysis, in which patients were classified into 2 groups according to their urinary sodium excretion at baseline, was conducted to determine the change from baseline in home BP profile at week 24. Results: At baseline, office systolic BP and morning, evening, and nocturnal home systolic BP were comparable between high urinary sodium excretion group (high group) and low urinary sodium excretion group (low group) (144.0 ± 19.7 vs 140.4 ± 18.4, P = 0.4044; 138.5 ± 12.1 vs 136.4 ± 16.6, P = 0.5179; 137.4 ± 17.6 vs 134.4 ± 17.3, P = 0.4481; 124.7 ± 14.8 vs 125.9 ± 14.9, P = 0.7267). The change in evening home systolic BP was greater in high group than in low group (-13.1 ± 12.0 vs -6.4 ± 11.4, P = 0.0203). The change in office BP, and morning and nocturnal home BP were comparable between high group and low group. Conclusions: In albuminuric DKD patients who have high dietary salt intake, add-on dapagliflozin treatment resulted in a greater decrease in evening home BP than in those who have low dietary salt intake.